Arabic Culture and Disagreements in Political TV Conversation - Hakim Rosly (Indonesian Journal of Arabic Studies, 2022)
In intercultural studies, Arabic society has been described as high-context culture that rely more on indirect message and little room is provided within verbalized articulations. This study attempts to prove out this basic insight relating to communication pattern of a culture in other settings, by analyzing Arabic disagreements in TV interaction. Little investigation about disagreements have been done in Arabic context. The current study will fill this gap and seeks to explore the realization of speech act of disagreement within the context of televised political discourse by analyzing and comparing direct and mitigated disagreement strategies in Arabic political TV talks. In order to achieve these research objectives, a total of twelve Arabic recorded TV programs were transcribed and analyzed through qualitative and quantitative methods. Disagreement responses in the corpus were classified and adjusted based on application framework suggested by some previous studies. The procedures for conducting this study involve data collection, transcription and analysis, using Conversation Analysis (CA) technique. This study reveales that the general percentage of direct disagreements were obviously higher and preferred to that of alleviated disagreements (64.9%-35.0%) which challenges the generalizations about cultural distinctions. Arabic disagreement features such as negation particle, explicit oppositional phrases and disagreement with apology were identified. When the Arab interactants engage in conflict, employing vocative particle with calling the name of the other speaker is one of the unique features found in this research. For future studies, researchers should be mindful of integrating polite and conflict framework for more comprehensive interpretation of human communication.Â